The Role of the Headman in Community Empowerment and Village Development Case Study: Harjamekar Village, North Cikarang District - Shalsa Aulia Setiawan; Lukmanul Hakim; Sopyan Resmana Adiarsa (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to find out and understand what are the policies and programs of the village head in implementing community empowerment village development, the strategies used by the village head for implementing village development and getting support/participation from the community as well as communication used as an instrument or tool to get input in the form of information in the decision-making process for the implementation of development in Harjamekar Village, North Cikarang District. This research method is qualitative with data collection techniques carried out through interviews, observation and documentation studies. The results of the research and discussion show that the village head's policies and programs in implementing village development and community empowerment in Harjamekar Village are making drainage nets, casting roads, repairing study rooms, and building bridges, while for community empowerment what is being done is implementing technical guidance programs, implementing work-intensive programs, provide socialization about employment. The village head's strategy in increasing community participation in development in Harjamekar Village is to build connections and commitment and align goals with the community regarding village development. The instrument or tool for obtaining input in the form of information in the decision-making process for the implementation of development in Harjamekar Village is through a deliberation mechanism